2013
DOI: 10.1093/europace/eut283
|View full text |Cite
|
Sign up to set email alerts
|

Clinical context and outcome of carotid sinus syndrome diagnosed by means of the 'method of symptoms'

Abstract: Carotid sinus massage by means of the 'method of symptoms' indentifies a clinical syndrome with definite features and outcome. A treatment strategy involving lifestyle measures, reduction of antihypertensive drugs and cardiac pacing when appropriate is effective in reducing the syncopal recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
1
22
1
1
Order By: Relevance
“…In the study of Gaggioli et al, 21 patients with carotid sinus syndrome and TT+ had a 2.7-fold increased risk of syncopal recurrence compared with carotid sinus syndrome and TT-: at a mean follow-up of 33 months, syncope recurred in 21% of 70 patients versus 9% of 99 patients (P=0.02); positive TT was the only independent predictor of syncopal recurrence. Solari et al, 22 in 141 patients affected by carotid sinus syndrome, found that a mixed or vasodepressor response to TT was the only independent predictor of syncopal recurrence (hazards ratio, 1.8; P=0.01). In conclusion, in the light of the present study and of the above literature, it is clear that cardiac pacing is effective when TT is negative, whereas syncope can frequently recur when TT is positive.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Gaggioli et al, 21 patients with carotid sinus syndrome and TT+ had a 2.7-fold increased risk of syncopal recurrence compared with carotid sinus syndrome and TT-: at a mean follow-up of 33 months, syncope recurred in 21% of 70 patients versus 9% of 99 patients (P=0.02); positive TT was the only independent predictor of syncopal recurrence. Solari et al, 22 in 141 patients affected by carotid sinus syndrome, found that a mixed or vasodepressor response to TT was the only independent predictor of syncopal recurrence (hazards ratio, 1.8; P=0.01). In conclusion, in the light of the present study and of the above literature, it is clear that cardiac pacing is effective when TT is negative, whereas syncope can frequently recur when TT is positive.…”
Section: Discussionmentioning
confidence: 99%
“…12 These data have been further supported by a later report from the same group, with more patients showing very similar findings. 13 The Italian SUP-2 study, including 10 Italian centres, recently reported a decision algorithm for older patients presenting clinically likely reflex syncope.…”
Section: Where We Are Nowmentioning
confidence: 99%
“…In a randomised controlled trial of withdrawal of psychotropic medications in 93 patients, Campbell et al 8 found a significant reduction in the risk of falling during 44 weeks of follow-up (1.16 vs 0.52 falls per person per year). In an acute randomised trial9 conducted on 32 patients affected by carotid sinus syncope, withdrawal of vasodilator therapy reduced the magnitude of the vasodepressor reflex induced by carotid sinus massage. This finding was confirmed by a recent observational study,10 which demonstrated that reducing/suspending vasoactive therapy in 96 patients affected by carotid sinus syndrome led to a reduction in the burden of syncope from a median of 0.5 syncopes per patient per year to a median 0 syncope per patient per year.…”
Section: Discussionmentioning
confidence: 99%